Athletes' use of reputation and gender information when forming initial expectancies of coaches - Manley, A.; Greenlees, I.; Thelwell, R.; Smith, M. (International Journal of Sports Science and Coaching, 2011)
This study aimed to investigate the impact of coach reputation and gender on athletes' expectancies of coaching competency. Male and female athletes (n = 304) viewed a coach profile (i.e., photograph and brief description of the target coach) before being asked to rate their expectancies of the coach's competency. Gender and reputation (i.e., successful vs. unsuccessful) of the target coach were manipulated. Multivariate and follow-up univariate analyses of variance revealed that successful coaches were rated as significantly more competent than unsuccessful coaches, while the female target coach was rated as significantly less competent than the male target coach on some competency dimensions. Athletes also reported that reputation influenced their expectancies more than gender. These findings indicate that athletes' expectancies of coaching competency are influenced by the coach's reputation and gender, but this impact appears to be more pronounced for reputation. Such results have implications for the development of effective coach-athlete relationships.